Balance recovery for lower limb exoskeleton in standing posture based on orbit energy analysis - Li, Mengze; Zhang, Bi; Liu, Ligang; Tan, Xiaowei; Li, Ning; Zhao, Xingang (Frontiers in Bioengineering and Biotechnology, 2024)
This paper addresses the essential need for standing balance in lower limb rehabilitation exoskeleton robots, aiming to enhance stability and safety. Innovatively, we introduce the 'Orbit Energy' (OE) metric, assessing the balance state of the human-exoskeleton system based on the position and velocity of the overall center of mass. Depending on the evaluation by OE, our framework is capable of selecting appropriate balance recovery strategies, including torque control for both ankle and hip joints. The effectiveness of our control algorithm is verified through Matlab Simulink simulations, analyzing balance recovery under various disturbance forces and ranges. Furthermore, experiments conducted with an actual exoskeleton robot further validate our framework, demonstrating a reduction in muscle activation during the maintenance of balance under external disturbances.